A survey on Fog Computing and its research challenges. (4th June 2020) - Machado, José Dos Santos; Moreno, Edward David; Ribeiro, Admilson De Ribamar Lima
This paper reviews the new paradigm of distributed computing, which is Fog Computing, and it presents its concept, characteristics and areas of performance. It performs a literature review on the problem of its implementation and analyses its research challenges such as: security issues; operational issues and their standardisation. We show and discuss that many questions need to be researched in academia so that their implementation will become a reality, but it became clear that their adherence is inevitable for the internet of the future.